Back for Good: Heterotopic Memory in Melbourne's Queer Nightlives. Issue 4 (December 2022) - Lynch, Regan Michael
Abstract : As venues shuttered across Australia, a fervent queer nightlife dreamed up new relations with virtuality, traversing the unstable terrains of memory and trauma. From reflections of sweaty dance floors to the 2020 Zoom-wave of internet performance, the mutual consideration of presence and lack both complexifies and reifies the stakes in reviving queer nightlife cultures.